2001
DOI: 10.1093/mutage/16.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis can be a confusing factor in in vitro clastogenic assays

Abstract: Among the tests used to determine the mutagenic potential of chemicals, the chromosomal aberrations and micronucleus assays play an important role. These tests score either chromosomal structural aberrations at metaphase or micronuclei at interphase. One of the hallmarks of apoptosis is DNA fragmentation into 50-300 kpb leading to oligonucleosomal fragmentation that can interfere with the results of clastogenic assays. In this case, apoptosis may be a confusing factor in the evaluation of the mutagenic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Consistent with our previous work [Meintieres et al, 2001], all the apoptosis inducers that are not genotoxins did not induce apoptosis in CTLL-2 bcl2 cells. Induction of micronucleated cells occurred only in the nontransfected cell line concurrently with the appearance of apoptosis.…”
Section: Ctll-2/ctll-2 Bcl2 Cell Lines Allow Distinction Between Apopsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous work [Meintieres et al, 2001], all the apoptosis inducers that are not genotoxins did not induce apoptosis in CTLL-2 bcl2 cells. Induction of micronucleated cells occurred only in the nontransfected cell line concurrently with the appearance of apoptosis.…”
Section: Ctll-2/ctll-2 Bcl2 Cell Lines Allow Distinction Between Apopsupporting
confidence: 92%
“…The purpose of this present study was to confirm and extend the results obtained in our previous study [Meintieres et al, 2001] by using additional agents. Furthermore, we wanted to improve the MN test performed in CTLL-2 and CTLL-2 bcl2 cells in order to develop a standardized protocol.…”
Section: Introductionsupporting
confidence: 84%
“…Clearly the number and classes of compounds analyzed needs to be expanded. Even so, these results are very encouraging, as the non-genotoxic cytotoxicants DEX and STS tend to be extreme challenges to mammalian cell genotoxicity assays [16][17]. Furthermore, we chose 24 hrs of continuous treatment as a particularly challenging experimental design to study, as previous work by lab L4 had demonstrated that assay specificity is reduced in this case [23].…”
Section: Discussionmentioning
confidence: 98%
“…Reports by Mentieres et al [16][17] and others suggest that the apoptotic program, perhaps especially nuclear fragmentation, can lead to the presence of MN-like events that may enhance the rate of false positive results. STS data presented here may represent a case in point, as elevated MN frequencies were observed by microscopy (L3).…”
Section: Apoptosis As a Confoundermentioning
confidence: 97%
“…The frequencies of micronucleated erythrocytes and leukocyte types were determined by randomly moving the field of view and counting 1000 erythrocytes on each slide using 10009 magnification under oil immersion. A micronucleus was identified as a small body that was adjacent but not connected to the principle nucleus (Meintieres et al 2001, Fig. 1).…”
Section: Micronucleus and White Blood Cell Testmentioning
confidence: 99%